AB0308 Spontaneous Ankle and Knee Fractures in Rheumatoid Arthritis: A CASE Report Study. (10th June 2014) - Yurtsever, A.; Rasmussen, C.
Abstract : Background: The occurrence of spontaneous extremity fractures in rheumatoid arthritis (RA) has been only occasionally reported in the medical literature [1]. New onset ankle or knee pains can be misinterpreted as arthritis activity by the clinicians and lead to potentially harmful intra-articular steroid injections. Objectives: The aim of this study is to describe the frequency and some clinical findings in patients with rheumatoid arthritis who have been diagnosed with knee or ankle fracture by MRI in a medium-sized Danish Department of Rheumatology. The findings may help clinicians to prevent, diagnose and treat such fractures better than today. Methods: The department cares for about 1.200 RA patients and all are prospectively registered twice a year in the clinical database DANBIO. The hospital IT-system codes MRI procedures and anatomical localization and the requesting department. Thus, it is possible to trace all MRI scans of knee and ankle in patients with rheumatoid arthritis. The inclusion criteria were patients diagnosed with RA and a fracture of the tibia, talus and calcaneus detected by MRI in 2010-2013. The exclusion criteria were obvious high-energy fractures. Results: Fifteen patients with spontaneous fracture in the ankle or knee were identified. They were all women aged between 61 and 89 years and they were diagnosed with RA through an average of 14, 2 years (1, 7-38, 6 years). 14/15 were either anti-CCP or IgM-RF positive. 14/15 were in DMARD methotrexate treatment (one in sulfasalazin). 4/15 were also in treatment with various biological agents. 11 patients had previously been in corticosteroid therapy >3 months and 2 of them ongoing. The patients present symptoms of relatively acute onset pain in the ankle or knee without any relevant trauma, while neither objective nor subjective findings suggestive of increased general arthritis activity. MRI was performed median 8 months (0, 9-21, 8) after the estimated fracture date. Eleven patients had previously been examined by conventional radiography, which could not detect the fracture. Two patients were not examined by X-ray before MRI and only in one patient the fracture was suspected after plain X-ray. Nine patients were treated by at least one intra-articular steroid injection after the fracture and before MRI. Ten of the patients experienced at least one fracture later and all patients, except one, had long-term pain and disability related to the fractures. Conclusions: When evaluating new onset ankle or knee pain in RA-patients, particularly in elderly female patients with longstanding disease, spontaneous fracture is a condition to consider, regardless of a normal conventional X-ray examination. In this study MRI imaging has proved useful in the detection of fractures in the knee and ankle. References: Resnick D, Cone R. Pathological fractures in rheumatoid arthritis: sites and mechanisms. RadioGraphics 1984. http://radigraphics.rsna.org/content/4/3/549.full.pdf Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5850